A scoping review of suicide prevention interventions for Latinx adults: strategies, gaps, and future directions - Airín D. Martínez; Samantha Kloft; Pablo Fernandez; Parastoo Dezyani; Alandra Ricci; Delvis J. Hernández; Kelley Cunningham (Frontiers in Public Health)
Suicide rates among Hispanic/Latina/o/x (Latinx) individuals in the United States have escalated significantly, becoming the fifth leading cause of death by 2020. This trend underscores the necessity for culturally responsive suicide prevention (SP) interventions tailored to Latinx persons’ unique sociodemographic characteristics. We synthesized the current literature on suicide prevention (SP) interventions for U.S. Latinx adults (18+ years). Our objective is to identify strategies, culturally sensitive approaches, and interventions that mitigate suicidal ideation, attempts, and deaths among Latinx adults. Following PRISMA guidelines, we conducted a comprehensive search across six electronic databases (CINAHL Complete, PubMed, PsycINFO, SocAbstracts, Sociology Database, and Web of Science), focusing on peer-reviewed articles published between 2000 and 2024 that described or evaluated SP approaches for Latinx adults (ages 18–64) in the United States. The review was structured according to the 2022 CDC Suicide Prevention Resources for Action, Strategies and Approaches to Suicide Prevention. Our search produced 4,739 articles, of which 155 were included for full-text review. During full-text review, 34 articles were included for the final sample. We randomly selected 10 articles and coded them to check for inter-rater reliability (r = 0.90). Analysis revealed that most SP interventions for U.S. Latinx adults align with the CDC strategy to “Identify and Support People at Risk.” The majority targeted late adolescents and early adults at the individual level. The predominant cultural adaptation was the translation of existing SP interventions into Spanish. These findings highlight the pressing need for more culturally responsive Latinx SP interventions that address other CDC strategies at the community and structural levels. Future research and intervention development should focus on creating comprehensive, culturally nuanced approaches that extend beyond individual-level interventions and language translation to address the complex factors contributing to Latinx adults’ suicide risk.